LDL-c Lowering, Ischemic Stroke and Small Vessel Disease Brain Imaging Biomarkers: A Mendelian Randomization Study - Dib, Marie-Joe (Stroke, 2024)
BACKGROUND: The effects of lipid-lowering drug targets on different ischemic stroke (IS) subtypes are not fully understood. We aimed to explore the mechanisms by which lipid-lowering drug targets differentially affect the risk of IS subtypes and their underlying pathophysiology. METHODS: Using a two-sample Mendelian randomization (MR) approach, we assessed the effects of genetically-proxied low-density lipoprotein cholesterol (LDL-c) and 3 clinically approved LDL-lowering drugs (3-hydroxy-3-methylglutaryl-CoA reductase, HMGCR; proprotein convertase subtilisin/kexin type 9, PCSK9 and Niemann-Pick C1-Like 1, NPC1L1) on stroke subtypes and brain-imaging biomarkers associated with small vessel disease (SVS), including white matter hyperintensity volume (WMHV) and perivascular spaces (PVS). RESULTS: In genome-wide MR analyses, lower genetically predicted LDL-c was significantly associated with a reduced risk of any stroke (AS), IS and large artery stroke (LAS), supporting previous findings. Significant associations between genetically predicted LDL-c and cardioembolic stroke (CES), SVS and biomarkers PVS and WMHV were not identified in this study. In drug-target MR analysis, genetically-proxied reduced LDL-c through NPC1L1 inhibition was associated with lower odds of PVS [Odds ratio (OR) per 1 mg/dL decrease = 0.79; 95% confidence interval (CI) = 0.67-0.93], and with lower odds of SVS [OR= 0.29, 0.10-0.85]. CONCLUSIONS: This study provides supporting evidence of a potentially protective effect of LDL-c lowering through NPC1L1 inhibition on PVS and SVS risk, highlighting novel therapeutic targets for SVS.